Pengembangan Media Video Animasi Berbasis Animaker pada Pembelajaran Tema 8 Subtema Perubahan Lingkungan - Dilla Nurillah Lestari; Irvan Permana; Ratih Purnamasari (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
This study aims to develop animated video media based on animaker in learning the theme of 8 sub-themes of environmental change in class V SD Negeri Kota Batu 08 knowing the effectiveness of the media, as well as knowing student responses to the media. This research is a type of research and development (RnD) or research and development according to the ADDIE model covering Analysis, Design, Development, Implementation, Evaluation. The product resulting from this research is animaker-based animated video media which was developed in the form of validation tests by media expert validators, linguists and material experts, and student response questionnaires and evaluations. In feasibility, the percentage of media experts is 92.8%, material experts are 78.1% and linguists are 87.2%. The results of the practicality of learning media with the Animaker application can be observed from student response questionnaires and evaluation results. The results of the study prove that the learning media with the Animaker application is feasible to use. Student responses prove a positive impact with the percentage of scores obtained. Based on the student response questionnaire of 71.7%, it can help in the learning process that is more interesting, effective and efficient.